Photocatalytic membrane reactors for water and wastewater treatment applications: process factors and operating conditions review - T.V. Tung; J. Ananpattarachai; P. Kajitvichyanukul (Lowland Technology International, 2018)
This paper aimed to overview of coupling photocatalytic process and membrane, known as photocatalytic membrane reactors (PMRs) and their potential applications in wastewater treatment, especially application for the decomposition of persistent organic matters. Mechanisms of PMRs for organic removal by photocatalytic and membrane processes are described. PMRs with suspended and immobilized TiO2 on/in the membrane are intensively reviewed. Several operating factors such as pH, initial TiO2 concentration, the concentration of pollutants, dissolved oxygen and aeration, hydraulic retention time as well as light intensity have been intensively discussed. Advantages and disadvantages of two types of PMRs are illustrated. This review is benefit to further future works such as up-scale PMRS to the industrial level, and the operating and maintenance needs for the effective PMRs.